Myeloid-Derived Suppressive Cells Deficient in Liver X Receptor α Protected From Autoimmune Hepatitis - Li, Bo; Lian, Min; Li, Yikang; Qian, Qiwei; Zhang, Jun; Liu, Qiaoyan; Tang, Ruqi; Ma, Xiong (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) emerge as a promising candidate for the immunotherapy of autoimmune hepatitis (AIH). However, targets for modulating MDSC in AIH are still being in search. Liver X receptors (LXRs) are important nuclear receptors linking lipid metabolism and immune responses. Despite of the extensive studies of LXR in myeloid compartment, its role in MDSC is currently less understood. Herein, expression of LXRα was found to be upregulated in AIH patients and co-localized with hepatic MDSCs. In ConA-induced hepatitis, deletion of LXRα led to increased expansion of MDSCs in the liver, and alleviated the hepatic injury. MDSCs in LXRα-/- mice exhibited enhanced proliferation and survival comparing with WT mice. T cell proliferation assay and adoptive cell transfer experiment validated the potent immunoregulatory role of MDSCs in vitro and in vivo. Mechanistically, MDSCs from LXRα-/- mice possessed significantly lower expression of interferon regulatory factor 8 (IRF-8), a key negative regulator of MDSC differentiation. Transcriptional activation of IRF-8 by LXRα was further demonstrated. Conclusion: We reported that abrogation of LXRα facilitated the expansion of MDSCs via downregulating IRF-8, and thereby ameliorated hepatic immune injury profoundly. Our work highlight the therapeutic potential of targeting LXRα in AIH.